Arabidopsis plants overexpressing additional copies of heat shock protein Hsp101 showed high heat tolerance and endo-gene silencing - Babbar, Richa (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.